Effects of tafamidis on exercise capacity, cardiac function and myocardial amyloid deposition in patients with transthyretin amyloid cardiomyopathy. (25th November 2020) - Rettl, R; Mann, C; Dachs, T; Duca, F; Binder, C; Dusik, F; Seirer, B; Badr Eslam, R; Hengstenberg, C; Bonderman, D
Abstract: Background: Transthyretin amyloid cardiomyopathy (ATTR-CA) is caused by deposition of amyloid fibrils in the myocardium. Tafamidis is a kinetic stabilizer of TTR that prevents tetramer dissociation and amyloidogenesis. Methods: Thirty-eight patients with diagnosis of ATTR-CA were treated with tafamidis (20mg or 61mg) for a period of six months. In our explorative analysis we aimed to evaluate the effects of tafamdis by changes from baseline of the serum NT-proBNP concentration, 6MWD, as well as cardiac structure and function, compared to untreated amyloidosis patients. Results: The analysis showed a significant reduction in the serum NT-proBNP concentration in tafamidis-treated patients compared to untreated patients (median difference, −1042.5 pg/mL, p=0.015). Tafamidis also improved the walking distance at month six, while reduction in untreated patients was observed (mean difference, +29.27 m, p=0.175). Echocardiographic findings revealed a decrease in LV size (mean, −1.56 mm) as well as improvements regarding the LA size (mean difference, −2.51 mm) and the GLS (mean difference, 0.80%) in tafamidis-treated patients. T1 mapping in cardiac MRI showed a decrease in ECV (mean, −1.79%) in patients receiving tafamidis, while an increase in ECV in untreated patients was observed (mean, +0.41%). Conclusion: Treatment with tafamidis for a period of six months in patients with ATTR-CA results in a significant improvement in NT-proBNP levels and may have positive effects on exercise capacity, cardiac function and myocardial amyloid deposition compared to untreated amyloidosis patients. Funding Acknowledgement: Type of funding source: None